Self-expanding metal stents versus TIPS in treatment of refractory bleeding esophageal varices: a systematic review and meta-analysis - Mohan, Babu P.; Chandan, Saurabh; Khan, Shahab R.; Kotagiri, Rajesh; Kassab, Lena L.; Olaiya, Babatunde; Ponnada, Suresh; Ofosu, Andrew; Adler, Douglas G. (Endoscopy International Open, 2020)
Background and study aims Refractory and recurrent esophageal variceal (EV) bleeding can be life threatening. Self-expanding metal stents (SEMS) have been used as a “bridge” therapy. However, their role in the treatment protocol is not established due to paucity in data.Methods We searched multiple databases from inception through May 2019 to identify studies that reported on SEMS and TIPS in refractory EV hemorrhage. Our primary goals were to analyze and compare the pooled all-cause mortality, immediate bleeding control and rebleeding rates.Results Five hundred forty-seven patients from 21 studies were analyzed (SEMS: 12 studies, 176 patients; TIPS: 9 studies, 398 patients). The pooled rate of all-cause mortality with SEMS was 43.6 % (95 % CI 28.6–59.8, I2  = 38) and with TIPS was 27.9 % (95 % CI 16.3–43.6, I2  = 91). The pooled rate of immediate bleeding control with SEMS was 84.5 % (95 % CI 74–91.2, I2  = 40) and with TIPS was 97.9 % (95 % CI 87.7–99.7, I2  = 0). The pooled rate of rebleeding with SEMS was 19.4 % (95 % CI 11.9–30.4, I2  = 32) and with TIPS was 8.8 % (95 % CI 4.8–15.7, I2  = 40).Conclusion Use of SEMS in refractory EV hemorrhage demonstrates acceptable immediate bleeding control with good technical success rate. Mortality and rebleeding rates were lesser with TIPS, however, its superiority and/ or inferiority cannot be validated due to limitations in the comparison methodology.